Hypoxic inhibition of human cardiac fibroblast invasion and MMP-2 activation may impair adaptive myocardial remodelling. (25th October 2007) - Morley, M.E.; Riches, K.; Peers, C.; Porter, K.E.
Abstract : Cardiac fibroblasts account for up to two-thirds of the total number of cells in the normal heart and are responsible for extracellular matrix homoeostasis. In vitro, type I collagen, the predominant myocardial collagen, stimulates proteolytic activation of constitutively secreted proMMP-2 (pro-matrix metalloproteinase-2). This occurs at the cell membrane and requires formation of a ternary complex with MT1-MMP (membrane-type-1 MMP) and TIMP-2 (tissue inhibitor of metalloproteinases-2). Following MI (myocardial infarction), normally quiescent fibroblasts initiate a wound healing response by transforming into a proliferative and invasive myofibroblast phenotype. Deprivation of oxygen to the myocardium is an inevitable consequence of MI; therefore this reparative event occurs under chronically hypoxic conditions. However, species and preparation variations can strongly influence fibroblast behaviour, which is an important consideration when selecting experimental models for provision of clinically useful information.